2014
DOI: 10.5194/amt-7-3113-2014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wind profiles from the NERC MST radar, Aberystwyth, UK

Abstract: Abstract. This study quantifies the uncertainties in winds measured by the Aberystwyth Mesosphere-StratosphereTroposphere (MST) radar (52.4 • N, 4.0 • W), before and after its renovation in March 2011. A total of 127 radiosondes provide an independent measure of winds. Differences between radiosonde and radar-measured horizontal winds are correlated with long-term averages of vertical velocities, suggesting an influence from local mountain waves. These local influences are an important consideration when usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In light of the fact that the correlations of the u and v components between different radar measurements are significantly high (0.95-0.99) and their RMSDs are also very consistent with each other (0.91-1.24 ms −1 ), it can be reasonably inferred that the RMSDs of the VHF radar-measured u and v components are comparable to those between different radar pairs. In this context, the RMSD of horizontal wind velocity related to the VHF radar measurements in the present study (approximately 0.956 ms −1 on average) is essentially consistent with that obtained by Lee et al [37].…”
Section: Comparisons Between Radar-measured Horizontal Windssupporting
confidence: 93%
See 2 more Smart Citations
“…In light of the fact that the correlations of the u and v components between different radar measurements are significantly high (0.95-0.99) and their RMSDs are also very consistent with each other (0.91-1.24 ms −1 ), it can be reasonably inferred that the RMSDs of the VHF radar-measured u and v components are comparable to those between different radar pairs. In this context, the RMSD of horizontal wind velocity related to the VHF radar measurements in the present study (approximately 0.956 ms −1 on average) is essentially consistent with that obtained by Lee et al [37].…”
Section: Comparisons Between Radar-measured Horizontal Windssupporting
confidence: 93%
“…They found that the RMSDs were between 0.8 ms −1 for low wind velocities (10-15 ms −1 ) below 5 km and 2.5 ms −1 for high winds (40-45 ms −1 ) at higher altitudes. As seen in Figure 5, the magnitudes of horizontal wind velocities for our cases are in the range of 5-17 ms −1 , which corresponds to the low wind velocity case defined by Lee et al [37]. In light of the fact that the correlations of the u and v components between different radar measurements are significantly high (0.95-0.99) and their RMSDs are also very consistent with each other (0.91-1.24 ms −1 ), it can be reasonably inferred that the RMSDs of the VHF radar-measured u and v components are comparable to those between different radar pairs.…”
Section: Comparisons Between Radar-measured Horizontal Windssupporting
confidence: 73%
See 1 more Smart Citation
“…mesosphere-stratosphere-troposphere (MST) radar techniques (e.g. Hooper et al, 2008;Lee et al, 2014) provide additional coverage over 0-20 km. Under clear-sky conditions the Rayleigh-Mie-Raman (RMR) lidar (Baumgarten, 2010;Hildebrand et al, 2012) measures winds throughout the middle atmosphere above Andenes, northern Norway but requires complex laser transmission and detection equipment and is not portable.…”
Section: Introductionmentioning
confidence: 99%
“…Among the capabilities of VHF-MST radar, continuous measurement of three-dimensional winds with a temporal resolution of several minutes and a vertical resolution of several hundred meters are praiseworthy (Lee et al, 2014). In addition to the air motion characterized by the wind field, small-scale structures of refractivity irregularities, such as thin layers with a thickness of tens of meters, exist commonly in the atmosphere and can reflect dynamic behavior of the atmosphere directly.…”
Section: Introductionmentioning
confidence: 99%